MODEL PENELITIAN HADIS MAHASISWA STRATA SATU UNIVERSITAS ISLAM NEGERI ALAUDDIN MAKASSAR TAHUN 2014-2019 - Tasbih; Mujadid Sigit Aliah (Jurusan Bimbingan dan Penyuluhan Islam, 2022)
This research discusses the study of hadith at state Islamic religious universities (a study of the trend of hadith studies at UIN Alauddin Makassar). The research method applied is qualitative, studying a social unit, including individuals, groups, institutions and communities. The results and discussion of this study indicate that thesis research model from 2014 to 2019 still dominates field studies. In addition, the most widely used model of hadith research is naqd al-hadith, followed by fiqh al-hadith, then living hadith, book study, and finally character/thought study. This research is expected to be one of the contributions to the study of hadith in Indonesia, especially to the study of hadith at the State Islamic Religious College (PTKIN). It can also be used as material for reflection on further studies. This research is a general study of hadith study models at UIN Alauddin Makassar so that in-depth and critical analysis has not been optimally found so this necessitates more comprehensive studies of hadith study models.